Combustion characteristics of crude tyre blends fuel in compression ignition engine - Ghimire, Subodh; Karn, Rupesh Lal; Bhatta, Khem Raj; Adhikari, Surya Prasad (Himalayan Journal of Applied Science and Engineering, 2024)
With the rise of automobile vehicles, the number of scrap tyres has been increasing rapidly. Proper management of waste tyre is challenging work for any country. Tyre oil possesses a greater potential of using as a substitute for conventional diesel. The investigation was made on the effects of blends of waste tyre fuel on combustion characteristics such as cylinder pressure (CP), net heat release rate (NHR), cumulative heat release (CHR), ignition delay (IGD), exhaust gas temperature (EGT), and % heat equivalent to brake power (HBP). It was found that crude tyre fuel has a low cetane index which affects the combustion characteristics. The two sample of test fuel were prepared by adding 5% crude tyre fuel to 95% diesel fuel (5BTF) and 10% crude tyre fuel to 90% diesel fuel (10BTF) by volume and their performance and emission characteristics were studied in a single cylinder four stroke diesel engine. For 10BTF, peak CP was reduced by 6.69%, IGD increased by 10.85%, NHR increased by 19.33% and there was a small difference in EGT with diesel. The opacity value of the blends of tyre fuel was found within the emission standard of Nepal. It is concluded that a blend of crude tyre pyrolysis oil up to 5% by volume with diesel shows similar combustion characteristics as that of diesel.